Park–people Conflict in Koshi Tappu Wildlife Reserve - Limbu, Kul Prasad; Karki, Toran Bahadur (Our Nature, 2006)
Conflict between people and wildlife is a major conservation issue that is difficult to resolve. It is difficult to decide what to do when the needs of people clash so directly with the needs of threatened species. The study was conducted in Paschim Kusaha VDC, adjoining area of Koshi Tappu Wildlife Reserve from Jan1997 to Jan1998 to identify the major conflict issues existing between reserve authorities and villagers. It was based on the observation and responses elicited from schedules that were distributed separately to the local people and reserve staff. Crop depredation and human harassment by wild animals were identified as a major problem to the villagers. Illegal activities of people in reserve area were the main problem for the management of reserve. The present study makes the recommendation to minimize the conflict, helps in the future planning programmes to the management policy and to the further research of this field. Keywords: Conflict, Koshi Tappu Wildlife Reserve, Crop depredation, Bubalus bubalis arnee doi:10.3126/on.v1i1.298 Our Nature (2003) 1: 15-18